2014
DOI: 10.1016/j.jecp.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Children’s classification and lexicalization of attractiveness, gender, and race: Differential displays of these concepts and relatedness to bias and flexibility

Abstract: Minimal research has examined children’s functional use of attractiveness to classify and label others, an important step in the development of children’s biases. This study compared 3-to 11-year-olds’ classification, sorting, and labeling of others and themselves based on attractiveness, gender, and race, and investigated whether these abilities and other characteristics predicted children’s bias and flexibility. Relative to gender and race, children rarely used attractiveness to spontaneously classify people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
(149 reference statements)
0
3
0
1
Order By: Relevance
“…Developmental theories and previous research have suggested that social categorization is a sufficient and necessary antecedent to intergroup bias and discrimination (Allen & Wilder, ; Bigler & Liben, ; Billig & Tajfel, ; Rennels & Langlois, ; Tajfel & Turner, ). Regarding explicit racial bias, a few studies have found it to be positively associated with children's social categorization skills (e.g., Bigler & Liben, ).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Developmental theories and previous research have suggested that social categorization is a sufficient and necessary antecedent to intergroup bias and discrimination (Allen & Wilder, ; Bigler & Liben, ; Billig & Tajfel, ; Rennels & Langlois, ; Tajfel & Turner, ). Regarding explicit racial bias, a few studies have found it to be positively associated with children's social categorization skills (e.g., Bigler & Liben, ).…”
mentioning
confidence: 95%
“…This is based on the findings of several existing studies examining the relation between children's social classification skills and their explicit social biases. For example, Rennels and Langlois () found that the number of dimensions (e.g., gender, race, and attractiveness) on which children could classify faces predicted their explicit gender bias. Moreover, Bigler and Liben () demonstrated that school‐aged children's ability to categorize people on various dimensions, such as race, gender, and age, predicted their explicit racial stereotypes.…”
mentioning
confidence: 99%
“…Stresszreakciók és a kommunikációs síkok (verbális és nonverbális) közötti diszharmóniák (megtévesztő jelzések) figyelmeztetésére elegendők. (Meyer, 2010) A szakirodalmakban ismertetett téves arcképfelismerések esetében érdemes megjegyezni, hogy a gyermekek legtöbbje erősen szimpátia és előítélet-vezérelt, amely megnöveli a téves választások számát (Rennels -Langlois, 2014), illetve amíg kérdéses a gyermek memóriaműködésének állapota, addig nem célszerű a Ki volt? vagy Ő volt?…”
Section: Kitekintés Egyéb Elemek Technikák: Harmadik Fél Információi Otthonlátogatásunclassified
“…For example, when 3-to 6.5-year-olds were asked what it means to be pretty or cute, the oldest aged girls provided the most detailed descriptions [48]. Similarly, when 3-to 11-year-olds were asked to sort and label pictures of peers based on attractiveness, girls were significantly more accurate at this task than boys [63].…”
Section: Middle Childhoodmentioning
confidence: 99%